Aktivitas K.H. Sholeh Abdul Hafidz dalam Mengembangkan Dakwah Islam di Kecamatan Rancakalong Kabupaten Sumedang Tahun 1957-1987 - Lutfa Munawar; Mahbub Hefdzil Akbar; Widiati Isana (Historia Madania: Jurnal Ilmu Sejarah, 2020)
The dissemination of Islamic da'wah in the area of Rancakalong District, Sumedang Regency, began in 1957. At the time, a kiai (Islamic scholar) came from the southern Sumedang aiming to spread the Islamic da'wah in Rancakalong District. Before his arrival, The religious conditions of Rancakalong people are not so prominent. Although at that time, the mosques already existed in several places, but there was no religious leader who could guide the community yet to be able to prosper the mosque and other forms of religious activities. The  was called K.H. Sholeh Abdul Hafidz. This study uses qualitative methods, namely data collection through interviews and documentation. The data analysis technique is done by the heuristic, criticism, interpretation, and historiography. The results of this study indicate that K.H. Sholeh Abdul Hafidz came to Rancakalong in 1957. The initial step of the preaching carried out by K.H. Sholeh Abdul Hafidz, began with his approach to the young and the old group of the community. The contribution form of his da'wah in Rancakalong District consisted of the establishment of the Bunsiari Islamic Boarding School I, then the Majelis Taklim of Bunsiari Islamic Boarding School I, and four Madrasa Diniyah Takmiliyah which were founded by K.H. Sholeh Abdul Hafidz’schildren.